Prevalence of potentially inappropriate medication use and drug utilization pattern in elderly patients: a prospective study from a tertiary care hospital - Kanagasanthosh, K.; Topno, Isabella; Aravindkumar, B. (International Journal of Research in Medical Sciences, 2017)
Background: To investigate the prevalence of potentially inappropriate medications (PIMs) using updated Beers criteria 2012 and drug utilization study among the elderly patients attending the various outpatient departments (OPDs) of a tertiary care hospital at Pondicherry in India. Methods: This prospective, observational study involving patients aged 65 years and above, was planned and conducted over a period of six months, who attended the various OPDs were included in the study. Prescriptions were collected from the consulting rooms and pharmacy. Results: A total of 600 patients aged 65 years and above were involved in our study. Majority (61.83%) were in the age group of 65-70 years. There was a male preponderance (61.83%). Total of 1769 drugs were prescribed, giving an average of 2.98 drugs per person (range 1 to 9). Polypharmacy (≥ 5drugs) were observed in 99 patients. Of the total 748 disease conditions, cardiovascular diseases were the most prevalent (29.33%) among the elderly patients. Almost 114 patients had comorbid conditions. General medicine department was the highest (28.83%) visited patients. Frequently prescribed drugs belong to the category of analgesic and anti-inflammatory agents (16.50%). Fixed Dose Combination (FDC) was 31%. Almost 110 patients received PIMs from Beers list; majority were belonging to category 1. NSAIDs (30.66%) were the highest PIMs prescribed to musculoskeletal disorders. With regard to WHO indicator, 377(21.31%) drugs were prescribed by generic name. Utilization from Indian national list of essential medicine was 76.82%. Percentage of encounters in which an antibiotic and injections was prescribed to 23.5% and 26.33% respectively. Conclusions: Study has shown the prevalence of disease pattern, comorbidity, drug usage in elderly. PIMs, polypharmacy and FDC were high among the elderly. Prescribers need to be educated about Beers criteria and encouraged for rational prescription.